2014
DOI: 10.1104/pp.114.247429
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Testa Rupture during Garden Cress Germination Involves Seed Compartment-Specific Expression and Activity of Pectin Methylesterases  

Abstract: Pectin methylesterase (PME) controls the methylesterification status of pectins and thereby determines the biophysical properties of plant cell walls, which are important for tissue growth and weakening processes. We demonstrate here that tissue-specific and spatiotemporal alterations in cell wall pectin methylesterification occur during the germination of garden cress (Lepidium sativum). These cell wall changes are associated with characteristic expression patterns of PME genes and resultant enzyme activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 62 publications
(82 reference statements)
3
76
0
Order By: Relevance
“…Database analysis has shown that 69 genes encode putative PMEIs/invertase inhibitors in Arabidopsis (Scheler et al 2014). Monocots have fewer PMEIs, consistent with remarks above; 35 genes encoding putative PMEIs were found in rice (Wang et al 2013b).…”
Section: Pectin Methylesterases (Pmes) and Their Inhibitors (Pmeis)supporting
confidence: 80%
See 3 more Smart Citations
“…Database analysis has shown that 69 genes encode putative PMEIs/invertase inhibitors in Arabidopsis (Scheler et al 2014). Monocots have fewer PMEIs, consistent with remarks above; 35 genes encoding putative PMEIs were found in rice (Wang et al 2013b).…”
Section: Pectin Methylesterases (Pmes) and Their Inhibitors (Pmeis)supporting
confidence: 80%
“…High PME activity is thus associated with the ABA-induced delay in radicle elongation and endosperm weakening; two processes that take place prior to the completion of germination (Müller et al 2006). In addition to the strong temporal regulation of PME and PMEI expression in seeds, PMEs and PMEIs have also been found to be differentially expressed in a tissue-specific manner during seed germination of the close Arabidopsis relative Lepidium sativum (Scheler et al 2014). In support of a role for PME activity and the resulting changes in DM in the timing and process of testa rupture, changes in expression were temporally focused around testa rupture (Scheler et al 2014).…”
Section: Seedsmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, monitoring of seed aging needs speedy viability analysis, which should be innovative, low-cost, and equally reliable (Dona et al, 2013). Current progress in genomics and seed biology has unraveled new horizons for efficient handling and conservation of ex-situ seed germplasm under extensive storage period (Scheler et al, 2015). Therefore, genomic and biochemical markers could be used to monitor seed aging; however, comprehensive knowledge of the complicated network of molecular and biochemical processes that mitigate seed longevity is needed in order to select appropriate markers, which can then be used to gather useful information about the aging and viability of ex-situ seed stocks.…”
Section: Genomics: a Hallmark To Monitor Molecular And Biochemical Prmentioning
confidence: 99%